Facial Paralysis and Communicative Participation: The Importance of Facial Symmetry at Rest. (August 2020) - Ayoub, Noel F.; Abdelwahab, Mohamed; Zhang, Michelle; Ma, Yifei; Stranberg, Sarah; Okland, Tyler S.; Pepper, Jon-Paul
Objective: There is a paucity of research devoted to understanding the communication restrictions encountered by facial paralysis patients. We aim to explore the relationship between patient-reported restrictions in communicative participation and objective facial paralysis severity using validated scales of facial movement. Methods: We performed a pilot retrospective study using a consecutive series of adult patients with a diagnosis of unilateral facial paralysis. In addition to baseline demographics, subjects were evaluated using the Communicative Item Participation Bank Short Form (CPIB), Electronic Facial Assessment by Computer Evaluation (eFACE), and Sunnybrook Facial Grading System (SFGS). Results: Twenty patients were included, 10 (50%) of whom were female with a mean age of 61 ± 13 years and mean duration of facial paralysis of 53 ± 82 months. The mean CPIB score was 14.6 ± 10.0 (range 0-29) and was comparable to scores of patients with conditions known to cause significant communicative disability. The mean eFACE scores were 67.4 ± 29.2, 44.2 ± 30.1, and 73.8 ± 30.0 for the static, dynamic, and synkinesis domains, respectively, with a composite smile score of 58.5 ± 16.9. After adjusting for age, gender, and duration of facial paralysis, significant moderate correlations were observed between the CPIB and the static eFACE domain ( r = –0.51, P = .03) and smile composite score ( r = 0.48, P = 0.0049), in addition to between the CPIB and SFGS synkinesis domain ( r = 0.48, P = 0.04). Conclusions: Patients with unilateral facial paralysis experience significant limitations in communicative participation. These restrictions demonstrate moderate to strong correlations with objective assessments of facial paralysis and quality of life measures. Communicative participation may be a helpful means of tracking response to treatment. Level of Evidence: IV